Long Term Study of Protective Mechanisms of Human Adipose Derived Mesenchymal Stem Cells on Cisplatin Induced Kidney injury in Sprague-Dawley Rats - Elhusseini, Fatma M (J Stem Cells Regen Med, 2016)
Background/Aims: Long-term evaluation of cisplatin induced nephrotoxicity and the probable renal protective activities of stem cells are lacking up until now. We evaluated the early and long-term role of human adipose derived mesenchymal stem cells (ADMSCs) in prevention or amelioration of cisplatin induced acute kidney injury (AKI) in Sprague-Dawley rats. For this, we determined the kidney tissue level of oxidative stress markers in conjugation with a renal histopathological scoring system of both acute and chronic renal changes. Methods: This study used eighty Sprague-Dawley (SD) rats weighing 250-300g. They were assigned into four equal groups (each group n=20): (I) Negative control group, rats injected with single dose of 1 ml normal saline. (II) Positive control cisplatin, rats injected with a single dose of 5 mg/kg I.P in 1 ml saline. (III) Cisplatin and culture media group, rats injected with 0.5 ml of culture media single dose into the tail vein and (IV) Cisplatin and ADMSCs group, rats injected with a single dose of 0.5 ml of culture media containing 5 x10(6)ADMSCs into the tail vein one day after cisplatin administration. Each main group was further divided according to the timing of sacrifice into four subgroups (each subgroup n=5). Rats in the subgroup A were sacrificed after 4 days; subgroup B were sacrificed after 7 days; subgroup C were sacrificed after 11 days; and subgroup D were sacrificed after 30 days. Before sacrifice, 24 hrs.-urine was collected using a metabolic cage. Renal function was evaluated through blood urea nitrogen (BUN), serum creatinine and creatinine clearance. Kidney tissue homogenate oxidative stress parameters, Malondialdehyde (MDA), Superoxide dismutase (SOD) and Glutathione (GSH) were determined. In addition, histopathological analysis for active injury, regenerative and chronic changes was performed. Results: ADMSCs were characterized and their capability of differentiation was proved. Cisplatin induced a significant increase in plasma creatinine and tissue MDA and induced a decrease in SOD, GSH and creatinine clearance. ADMSCs attenuated these changes. Cisplatin resulted in prominent histopathological changes in the term of tubular necrosis, atrophy, inflammatory cells infiltration and fibrosis. ADMSCs significantly lowered the injury score at day 4, 7, 11 and 30 with marked regenerative changes starting from day 4 and limited fibrotic score at day 30. Conclusion: ADMSCs have both protective and regenerative abilities with consequent limitation of the development of renal fibrosis after the cisplatin induced acute tubular necrosis, largely through an anti-oxidative activity.